2000
DOI: 10.1074/jbc.275.2.809
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glu192 in the Allosteric Control of the S2′ and S3′ Subsites of Thrombin

Abstract: Thrombin is an allosteric protease controlled through exosites flanking the catalytic groove. Binding of a peptide derived from hirudin (Hir 52-65 ) and/or of heparin to these opposing exosites alters catalysis. We have investigated the contribution of subsites S 2 and S 3 to this allosteric transition by comparing the hydrolysis of two sets of fluorescence-quenched substrates having all natural amino acids at positions P 2 and P 3 . Regardless of the amino acids, Hir 52-65 decreased, and heparin increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 67 publications
(308 reference statements)
3
13
0
1
Order By: Relevance
“…Similar effects were thus obtained with both reptilase and thrombin, supporting the hypothesis that PF4 interacted with fibrinogen and/or fibrin; alternately, PF4 would have to affect both proteases through discrete allosteric alterations. The rates of H-DPhe-Pro-Arg-pNA hydrolysis by either thrombin or reptilase were unaffected by large amounts of PF4 or poly-L-lysine and only marginally affected by Polybrene (data not shown), rendering it unlikely that the impact of PF4 on clot formation was mediated through allosteric alteration (39). That the effect of PF4 resulted from a specific interaction and not from an incompletely controlled parameter was also attested by the observation that a stoichiometric amount of an anti-PF4 antibody attenuated the effect of PF4 by 75% ( Fig.…”
Section: Physiologic Amounts Of Pf4 Alter the Rate Of Formation Of Fimentioning
confidence: 99%
“…Similar effects were thus obtained with both reptilase and thrombin, supporting the hypothesis that PF4 interacted with fibrinogen and/or fibrin; alternately, PF4 would have to affect both proteases through discrete allosteric alterations. The rates of H-DPhe-Pro-Arg-pNA hydrolysis by either thrombin or reptilase were unaffected by large amounts of PF4 or poly-L-lysine and only marginally affected by Polybrene (data not shown), rendering it unlikely that the impact of PF4 on clot formation was mediated through allosteric alteration (39). That the effect of PF4 resulted from a specific interaction and not from an incompletely controlled parameter was also attested by the observation that a stoichiometric amount of an anti-PF4 antibody attenuated the effect of PF4 by 75% ( Fig.…”
Section: Physiologic Amounts Of Pf4 Alter the Rate Of Formation Of Fimentioning
confidence: 99%
“…Thrombin-In a previous study (29), we reported selectivity indexes of 636 and 20 in S 2 Ј for thrombin and trypsin, respectively. Accordingly, S 2 Ј of FXa would have a selectivity comparable with that of trypsin.…”
Section: The Catalytic Groove Of Fxa Behaves More As a Low Efficient mentioning
confidence: 99%
“…Therefore, three additional series of substrates were synthesized to fulfill the thrombin study; they had ABz-VGPRSFRDQ-EDDnp for a common framework in the P 2 and P 3 series and ABz-VGPRSFLDQ-EDDnp in the P 1 Ј series. Also, the values listed for thrombin concerning the P 2 Ј and P 3 Ј series are taken from Marque et al (29); they were obtained with fluorescence-quenched substrates having ABz-VGPRSFLLK(DNP)D for a common framework. Amino acids in P 3 , P 2 , P 1 Ј, P 2 Ј, or P 3 Ј that varied within each series are listed together with the estimated value of k cat /K m (in M Ϫ1 s Ϫ1 ) representing the weighted mean of at least three determinations (final standard errors were 20% or less).…”
Section: Table II Values Of K Cat /K M For the Cleavage Of Fluorescenmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence quenched peptide substrates [6] spanning both sides of the scissile bond (P 1 -P 1 ') were used to investigate such P' specificities in a similar way to that used for other proteases [7,8]. These probes contain an N-terminal 2-aminobenzoyl (Abz) group and a penultimate 2,4-dinitrophenyl (Dnp) derivitized lysine (e.g.…”
Section: Introductionmentioning
confidence: 99%